Serum undercarboxylated osteocalcin is a marker of the risk of hip fracture in elderly women. - Szulc, P (1993)
It has been previously shown that the level of circulating undercarboxylated osteocalcin (ucOC) is elevated in elderly women in comparison with young, healthy, premenopausal ones. To understand the mechanism of the increase in the ucOC in the elderly and to assess its potential consequences on bone fragility, we have measured ucOC in the sera of 195 elderly institutionalized women 70-101 yr of age. In 45 women (23%) serum ucOC was above the upper limit of the normal range for young women. The level of ucOC was negatively correlated with 25OHD (r = -0.32, P < 0.001) even after excluding the effect of age, parathyroid hormone (PTH), and creatinine by partial correlation (r = -0.24, P < 0.002). During an 18-mo follow-up, 15 women sustained a hip fracture and their baseline ucOC level was higher (P < 0.01) in women who subsequently sustained hip fracture than in the nonfracture group contrasting with no significant differences for serum calcium, phosphate, alkaline phosphatase, creatinine, PTH, 250HD, and total and carboxylated OC. The risk of hip fracture was increased in women with elevated ucOC (relative ratio 5.9, 99.9% Cl 1.5-22.7, P < 0.001). During 1 yr of calcium/vitamin D2 treatment, ucOC decreased (P < 0.05), especially in those with the initially increased values (from 2.22 +/- 0.35 to 1.41 +/- 0.29 ng/ml, P <0.005) contrasting with an increase in the placebo group (P < 0.05). In conclusion, the increase in ucOC in the elderly reflects not only some degree of vitamin K deficiency but also their poor vitamin D status, suggesting that vitamin D may be important, either directly or indirectly through its effect on bone turnover, for achieving a normal gamma-carboxylation of OC. The ucOC, but not conventional calcium metabolism parameters, predicts the subsequent risk of hip fracture, suggesting that serum ucOC reflects some changes in bone matrix associated with increased fragility.